Teacher Education in Portugal - Ruivo, João (2019)
The teacher education is a period of great moments of rupture, which relate to the need of giving voice and working conditions to the movements of innovation and pedagogical renewal, who pretend to transmit new representations and positive expectations. Train teachers for the millennium and the knowledge society, where combat digital illiteracy is assumed to be urgent concern is a task that motivates educational reform movements that cross the world. However, this reform movement, should also mean that believes not only in the initial training - first step to permanently downgrade - which must be exhausting efforts personal, professional, institutional, political, budgetary and financial these new winds of reformism educational and systemic. Should mean, above all, a commitment to the teacher education, in response to the challenge of breaking the commonplace to recognize in theory its importance but simultaneously attend to the placing of obstacles to its implementation in schools. This chapter intends to describe the evolution of Teacher Education in Portugal, in the context of these variables, following a diachronic line, with emphasis on the current situation.